2011
DOI: 10.1038/sc.2011.58
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury sequelae alter drug pharmacokinetics: an overview

Abstract: Study design: Literature review. Objectives: Critical review of the literature published on the physiological alterations caused by spinal cord injury (SCI) and their effect on the pharmacokinetic parameters of commonly employed drugs. The review introduces the most recent treatment protocols of a variety of drugs, enabling the modern clinician to apply efficacious and cost-effective solutions to the pharmacological treatment of SCI patients. Methods: Studies published in international indexed journals up to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Predicting optimal dosing regimens is also difficult because of the altered muscle mass and physiological changes affecting drug absorption, distribution, metabolism, and excretion. 13 These endogenous changes are independent of the drug-drug interactions and clinical conditions that require personal attention to each regimen. Patients also frequently self-medicate using alternative medications and over the counter products further complicating interpretation of patient responses to prescribed medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting optimal dosing regimens is also difficult because of the altered muscle mass and physiological changes affecting drug absorption, distribution, metabolism, and excretion. 13 These endogenous changes are independent of the drug-drug interactions and clinical conditions that require personal attention to each regimen. Patients also frequently self-medicate using alternative medications and over the counter products further complicating interpretation of patient responses to prescribed medications.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental assumptions of pharmacokinetics and pharmacodynamics derived from clinical studies on able-bodied individuals do not apply to this population. 12,13 In many cases, the standard dosing schedules may not achieve the anticipated concentration of the drug, leading to under treatment or potentially supratherapeutic levels leading to adverse events. 6,14,15 In addition, medications required for managing comorbidities following SCI often have overlapping pharmacological mechanisms or targets creating even higher risks for DRPs.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,41 Based on the knowledge of SCI effects on the pharmacokinetics of drugs reported in the past 26 years (1985-2011), 3,14,18,23,27,35,39,44,[46][47][48]55 we may anticipate the following alterations of pharmacokinetics of riluzole in patients with acute SCI from that in healthy individuals.…”
Section: Alterations Of Pharmacokinetics Of Drugs In Scimentioning
confidence: 99%
“…4 This is of particular interest as drug metabolism can be altered by the SCI making it more difficult to predict its effects. 9 Furthermore, different medications used to manage symptoms of coexisting conditions may cause opposing physiological effects, potentially reducing the therapeutic efficacy of the medications used. For example, approximately one-fourth of our study population was found to take BladM and BwlA concomitantly; the antimuscarinic action of BladM, which aim to inhibit involuntary bladder contractions and thus manage urinary incontinence, can also inhibit bowel motility potentially aggravating constipation symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…8 Predicting the possibility of adverse drug effects is more challenging in SCI because drug pharmacokinetics can be altered following the injury and the degree of alteration can vary depending on the level and severity of SCI. 9 Moreover, with age-related diseases and SHCs increasing over time in persons with SCI, [10][11][12] the likelihood of requiring multiple medications also increases, adding to the risk of adverse drug effects.…”
Section: Introductionmentioning
confidence: 99%